Child labor and associated risk factors in the wake of the COVID-19 pandemic: a scoping review - Habib, Rima R.; El Khayat, Moussa; Ghanawi, Joly; Katrib, Reem S.; Hneiny, Layal; Halwani, Dana A. (Frontiers in Public Health, 2024)
Child labor can significantly impact the health, welfare, and development of children engaged in labor. The spread of child labor around the globe is predicted to accelerate as a consequence of the COVID-19 pandemic. To this end, a scoping review was conducted to (a) synthesize emerging themes and results from recent research on child labor during the COVID-19 pandemic, (b) identify factors that increase the risk of children falling into child labor and (c) provide recommendations that can inform the development of policies and programs to ensure that previous efforts to combat child labor are not lost. Six electronic databases (Medline, EMBASE, Scopus, CINAHL, Global health, and Web of Science) were searched on January 21, 2022. The database searches, along with the grey literature search, identified 5,244 studies, of which 45 articles were included in the final review. Several of those articles (8 of 45 articles) reviewed concluded that the pandemic could increase child labor worldwide including the worst forms of child labor. The reviewed studies identified primary risk factors for child labor during the COVID-19 pandemic including economic challenges, temporary school closure and a greater demand for child labor, mortality among parents, and limited social protection. This scoping review identified the need for more field research on child labor following the COVID-19 pandemic to detect emerging patterns of child labor and to develop effective intervention measures. There is also a need for further empirical research on the consequences of the COVID-19 pandemic on gender differences in occupational exposure and health outcomes among working children and marginalized groups such as migrants, refugees, and minority groups. Based on the conclusions drawn from this review, it is evident that addressing child labor in the wake of the pandemic necessitates a multi-sectoral response by the government, businesses, civil society, and funding/donor agencies. This response should address various areas such as education, social and child protection, and legislation to support vulnerable children and their families in order to combat child labor subsequent to the pandemic.